2019
DOI: 10.3389/fpsyg.2019.02703
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Happiness to Teachers - Development and Evaluation of a Training in Subjective Well-Being

Abstract: Teachers’ health is a persistent challenge for educational systems all over the world. Moreover, research results – especially in the domain of positive psychology – indicate that high levels of well-being are associated with additional benefits improving teachers’ professional performance. Therefore, a training to foster subjective well-being with one training day, two booster sessions, and exercises before, during, and after the meetings was developed. It consisted of about 10 h of face-to-face time and abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 86 publications
3
46
0
Order By: Relevance
“…Furthermore, these studies have not adopted the entire CIT scale, but only a few subscales of the CIT. Instead, an extensive use of BIT is registered, both to measure well-being in cross-sectional study (e.g., Duan et al, 2018;Höfer et al, 2019;Ugwu et al, 2018) and to assess the effectiveness of welfare interventions, such as a therapeutic horticulture intervention with child survivors of sexual abuse (Watkins et al, 2019), a 9-week trauma and resilience curriculum with high school students (Judge, 2018), a single-session positive cognitive intervention as well as a character strength-based intervention with first-year university students , a fourteen-module video-recorded well-being intervention with undergraduate students (Singh & Bandyopadhyay, 2020), a group intervention for refugees and asylum seekers (Reebs et al, 2020), and a training to foster teachers' well-being (Rahm & Heise, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these studies have not adopted the entire CIT scale, but only a few subscales of the CIT. Instead, an extensive use of BIT is registered, both to measure well-being in cross-sectional study (e.g., Duan et al, 2018;Höfer et al, 2019;Ugwu et al, 2018) and to assess the effectiveness of welfare interventions, such as a therapeutic horticulture intervention with child survivors of sexual abuse (Watkins et al, 2019), a 9-week trauma and resilience curriculum with high school students (Judge, 2018), a single-session positive cognitive intervention as well as a character strength-based intervention with first-year university students , a fourteen-module video-recorded well-being intervention with undergraduate students (Singh & Bandyopadhyay, 2020), a group intervention for refugees and asylum seekers (Reebs et al, 2020), and a training to foster teachers' well-being (Rahm & Heise, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The well-being of clients/ patients should be evaluated pre-and post-treatment using comprehensive scales which are able to assess diverse well-being dimensions at once. We suggested to use the Brief Inventory of Thriving because (1) it assesses numerous dimensions of well-being (life satisfaction, optimism, positive emotion, belonging, support, self-worth, flow, accomplishment, meaning and purpose) using only 10 items; (2) its test-retest reliability has been demonstrated in different studies (e.g., Sorgente et al, 2018;Su et al, 2014); (3) it is commonly adopted to evaluate the efficacy of treatments (e.g., Judge, 2018;Rahm & Heise, 2019;Reebs et al, 2020;Singh & Bandyopadhyay, 2020;Watkins et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of the PPIs that are especially designed for school teachers are largely unknown. Some previous studies indicated the advantageous effects of PPIs in promoting well-being and minimising teacher stress (Chan 2010(Chan , 2013McCullough 2015;Rahm and Heise 2019). However, the findings and their generalisability are limited due to the described shortcomings of the study and intervention designs.…”
Section: Research Question and Hypothesismentioning
confidence: 96%
“…A few studies have begun to highlight the potential value of PPIs for teachers (Chan 2010(Chan , 2013McCullough 2015;Rahm and Heise 2019). These studies have investigated the effects of standard strength-, savouring-, and gratitude-based interventions on teachers, which proved effective to some extent.…”
Section: Ppis For Teachersmentioning
confidence: 99%
See 1 more Smart Citation